Two isoprenylated flavonoids from Dorstenia psilurus activate AMPK, stimulate glucose uptake, inhibit glucose production and lower glycemia. Issue 24 (17th December 2019) - Choumessi, Aphrodite T.; Johanns, Manuel; Beaufay, Claire; Herent, Marie-France; Stroobant, Vincent; Vertommen, Didier; Corbet, Cyril; Jacobs, Roxane; Herinckx, Gaëtan; Steinberg, Gregory R.; Feron, Olivier; Quetin-Leclercq, Joëlle; et al.
Abstract : Root extracts of a Cameroon medicinal plant, Dorstenia psilurus, were purified by screening for AMP-activated protein kinase (AMPK) activation in incubated mouse embryo fibroblasts (MEFs). Two isoprenylated flavones that activated AMPK were isolated. Compound 1 was identified as artelasticin by high-resolution electrospray ionization mass spectrometry and 2D-NMR while its structural isomer, compound 2, was isolated for the first time and differed only by the position of one double bond on one isoprenyl substituent. Treatment of MEFs with purified compound 1 or compound 2 led to rapid and robust AMPK activation at low micromolar concentrations and increased the intracellular AMP:ATP ratio. In oxygen consumption experiments on isolated rat liver mitochondria, compound 1 and compound 2 inhibited complex II of the electron transport chain and in freeze–thawed mitochondria succinate dehydrogenase was inhibited. In incubated rat skeletal muscles, both compounds activated AMPK and stimulated glucose uptake. Moreover, these effects were lost in muscles pre-incubated with AMPK inhibitor SBI-0206965, suggesting AMPK dependency. Incubation of mouse hepatocytes with compound 1 or compound 2 led to AMPK activation, but glucose production was decreased in hepatocytes from both wild-type and AMPKβ1 −/− mice, suggesting that this effect was not AMPK-dependent. However, when administered intraperitoneally to high-fat diet-induced insulin-resistant mice, compound 1 and compound 2 had blood glucose-lowering effects. In addition, compound 1 and compound 2 reduced the viability of several human cancer cells in culture. The flavonoids we have identified could be a starting point for the development of new drugs to treat type 2 diabetes.